Clinical Features and Treatments of Syphilitic Uveitis: A Systematic Review and Meta-Analysis - Ting Zhang; Ying Zhu; Gezhi Xu (Journal of Ophthalmology)
Purpose. To investigate the clinical features and efficacies of treatments for syphilitic uveitis. Methods. PubMed was searched for studies of syphilitic uveitis published between January 1990 and October 2016. The clinical features were summarized and appraised. The pooled success rate was defined as an improved or maintained final visual acuity and was calculated with 95% confidence intervals (CIs). Heterogeneity, subgroup analysis, sensitivity analysis, and publication bias were assessed. Results. Thirty-two studies involving 670 patients were analyzed. The most common type of syphilitic uveitis was papillitis. The pooled success rate was 0.91 (95% CI 0.84–0.97) for antibacterial agents alone (15 studies, 286 patients); 0.95 (95% CI 0.91–0.98) for antibacterial agents and systemic corticosteroids combined (11 studies, 245 patients); and 0.91 (95% CI 0.80–0.98) for antibacterial agents, systemic corticosteroids, and other immunosuppressants combined (3 studies, 73 patients). Subgroup analyses revealed no correlations of the efficacy of antibacterial agent monotherapy with study characteristics, such as human immunodeficiency virus coinfection status. Conclusions. This systematic review and meta-analysis revealed the efficacy of antibacterial agents for treating syphilitic uveitis. Coadministration of systemic corticosteroids or immunosuppressants did not elicit further improvements in the clinical outcomes of antibacterial agents.